Dampak Covid-19 terhadap Fluktuasi Harga Saham dan Volume Transaksi Saham pada Perusahaan Subsektor Telekomunikasi Yang Terdaftar di Bursa Efek Indonesia - Listya Devi Junaidi; Lukman Hakim Siregar; Malesa Anan (Ekonomis: Journal of Economics and Business, 2021)
The impact of the spread of the COVID-19 outbreak is not only detrimental to human health but also detrimental to the country's economy both domestically and abroad. After the announcement of the entry of this outbreak to Indonesia on March 2, 2020, the government tried to make various efforts to reduce the spread of this virus, namely by conducting social distancing, work from home (WFH) and, teaching and learning activities from home. This activity requires people to always be in touch with electronic media such as laptops, smartphones, etc. However, this situation has benefited subsector Telecommunication companies where the need for internet services is increasing. This study aims to determine how the comparison of stock prices and share transaction volume in telecommunication sub-sector companies before and after the announcement of the spread of COVID-19 in Indonesia. This research uses A normality test and hypothesis test Paired Sample T-Test. The results of this study indicate that COVID-19 has a significant impact on the value of stock prices and the volume of stock transactions in the telecommunications sub-sector where the value of stock prices and the volume of stock price transactions that had previously increased but decreased.